2018
DOI: 10.1039/c7cp05484j
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the effect of a non-aqueous proton donor on electrochemical ammonia synthesis

Abstract: Ammonia synthesis is one of the most studied reactions in heterogeneous catalysis. To date, however, electrochemical N reduction in aqueous systems has proven to be extremely difficult, mainly due to the competing hydrogen evolution reaction (HER). Recently, it has been shown that transition metal complexes based on molybdenum can reduce N to ammonia at room temperature and ambient pressure in a non-aqueous system, with a relatively small amount of hydrogen output. We demonstrate that the non-aqueous proton do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 53 publications
0
73
1
Order By: Relevance
“…However, RuS 2 is also expected to contribute to some hydrogen evolution that can decrease the yield of ammonia if used in aqueous electrolytes. However, using non‐aqueous electrolytes like 2,6‐lutidinium (LutH + ) or titanocene dichloride [(η5‐C 5 H 5 ) 2 TiCl 2 ] might attenuate the HER, and thus not affect the yield of ammonia considerably.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, RuS 2 is also expected to contribute to some hydrogen evolution that can decrease the yield of ammonia if used in aqueous electrolytes. However, using non‐aqueous electrolytes like 2,6‐lutidinium (LutH + ) or titanocene dichloride [(η5‐C 5 H 5 ) 2 TiCl 2 ] might attenuate the HER, and thus not affect the yield of ammonia considerably.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly,i tw as found that RuS 2 is the mosta ctives ulfide with an overpotential of only 0.29 V. Although this sulfide can contributet of ormation of hydrogen as well and, thus, lower the yield of ammonia formation in experiments,t his should not diminish the importance of RuS 2 for further experimental investigations.F or example, RuS 2 can be tested experimentally with the use of non-aqueous electrolytes like 2,6-lutidinium (LutH + ) [53] or titanocene dichloride ((h5-C 5 H 5 ) 2 TiCl 2 ) [54] to attenuate the HER. Another interesting observation is that on all the NiAs-type structures as wella st he pyrite RuS 2 ,t he step associated with the NNH 3 formation does thermodynamically lead to dissociation of the NÀNb ond and formation of Na nd NH 3 .T hus, dinitrogen dissociation should be relativelyf acile on these sulfide surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, to increase the hydrogen evolution energy barrier, 2,6‐lutidinium (LutH + ) can be utilized instead of hydronium, as suggested by theoretical calculations. This led to a higher barrier for HER on the electrocatalyst surface via the Volmer process . In addition to regulating the electrolyte for controlling the catalyst/electrolyte interface, engineering the electrocatalyst surface such that it is hydrophobic and repels hydrogen, is also a useful strategy for promoting NRR.…”
Section: Electrochemical System Engineeringmentioning
confidence: 99%